Maternal omentin-1 level, quality of life and marital satisfaction in relation to mode of delivery: a prospective cohort study - Simin Parvanehvar; Najmeh Tehranian; Anoshirvan Kazemnejad; Hossein Mozdarani (BMC, 2020)
Abstract Background The purpose of this study was to evaluate the maternal omentin-1 level, quality of life and marital satisfaction of women with cesarean and vaginal delivery. Methods This prospective cohort study was conducted on 45 women with elective cesarean delivery and 45 women with vaginal delivery who referred to a public hospital in Tehran, Iran. Maternal omentin-1 level was measured by ELISA kits within 24 h after delivery. The maternal quality of life and marital satisfaction in the third trimester of pregnancy and at 12 weeks postpartum were measured using WHOQOL-BREF and the Kansas marital satisfaction questionnaires, respectively. For making between-groups and within-groups comparison, independent samples t-test, paired samples t-test and chi-square test were applied accordingly. Results The level of maternal omentin-1 was reported to be higher in vaginal delivery group compared to the cesarean group (p = 0.02). No significant difference was found in the quality of life between the two groups in the third trimester of pregnancy and at 12 weeks postpartum period. However, women in both groups had lower scores in physical dimension at 12 weeks postpartum compared to the third trimester of their pregnancy [mean ± SD in vaginal group = 59.28 ± 15.5 vs. 64.44 ± 15.05, p = 0.003 and mean ± SD in cesarean group = 60.07 ± 14.84 vs. 66.50 ± 11.32, p <  0.001]. The results of paired samples t-test indicated that women in NVD group had significantly higher psychological wellbeing at 12 weeks postpartum compared to the third trimester of pregnancy [mean ± SD 68.9 ± 16.82 vs. 65.73 ± 16.87, p = 0.001]. There was no significant difference in marital satisfaction between the two groups at 12 weeks postpartum (P = 0.07). The results of paired samples t-test showed that women in CS group had significantly lower marital satisfaction at 12 weeks postpartum compared to the third trimester of pregnancy [mean SD 18.86 ± 2.04 vs. 19.28 ± 1.79, p = 0.01]. Conclusions Our findings demonstrated that women with NVD had higher omentin-1 level than women with CS. No significant difference was found in quality of life and marital satisfaction between NVD and CS and omentin-1 level. High level of omentin-1 in NVD may act as a protective factor for mother against metabolic disorders.